The Impact of Cognitive, Digital, and Psychological Factors on Risky Investment Decisions among Generation Z Investors in Indonesia: The Role of Economic Capability - Ni Wayan Dian Irmayani; Nyoman Sri Subawa; Ida Ayu Oka Martini; Luh Putu Mahyuni (Greenation Research & Yayasan Global Resarch National, 2026)
The rapid growth of digital technology and online investment platforms has significantly increased Generation Z participation in risky investment activities in Indonesia. As digital natives, Generation Z relies heavily on digital information, social media, and financial influencers when making investment decisions. However, investment behavior is influenced not only by knowledge and information but also by psychological and economic factors. This study aims to analyze the effects of financial literacy, digital literacy, perceived trust, financial influencers, psychological bias, and risk attitude on risky investment decisions among Generation Z investors in Indonesia. Furthermore, the study examines the moderating role of economic capability in strengthening the relationships between behavioral factors and risky investment decisions. This research employs a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to Generation Z investors and analyzed using Structural Equation Modeling. Using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with data from 275 Generation Z investors across six Indonesian regions, the model explained 63.6% of the variance in risky investment decisions (R² = 0.636; Q² = 0.564; GoF = 0.586). Financial literacy was the only determinant with a significant individual path effect (β = 0.192; p = 0.049). Because the behavioral constructs were highly intercorrelated, the study applied an inferential triangulation strategy combining individual-path testing with block-level hierarchical regression. This revealed that the cognitive-capability block (financial and digital literacy) and the psychological-behavior block (psychological bias and risk attitude) contributed significant incremental variance, whereas perceived trust and financial influencers did not. Economic capability operated as a dominant direct predictor (explaining 53.2% of baseline variance) rather than as a moderator; none of its three moderating effects was significant. The findings indicate that risky investment decisions among Generation Z are driven primarily by internal cognitive and behavioral dispositions operating as an integrated cluster rather than by external social influences, contributing methodological and contextual insights to behavioral finance literature.